2019
DOI: 10.1016/j.antiviral.2018.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Third Tofo Advanced Study Week on Emerging and Re-emerging Viruses, 2018

Abstract: Singapore, and the USA. Meeting sessions covered aspects of the epidemiology, diagnosis, molecular and structural biology, vaccine development, and antiviral drug discovery for emerging RNA viruses that are current threats in Africa and included flaviviruses (dengue and Zika), alphaviruses (chikungunya), coronaviruses, filoviruses (Ebola), influenza viruses, Crimean Congo hemorrhagic fever virus, Rift Valley fever Virus, Lassa virus, and others. Data were presented on recent flavivirus and/or chikungunyavirus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…India's response to such acute public health emergency demonstrates the inadequate capacity of most dengue endemic countries (like Thailand, Cambodia, Bangladesh and Nigeria) in handling outbreaks and points to a healthcare system that is chronically underfunded, unregulated, and has inadequate infrastructure [49]. A similar study has confirmed a high societal and individual family burden of dengue in Cambodia [50].The emergence and reemergence of other viruses like filoviruses (Ebola) and coronaviruses (Covid-19) has strongly made the situation worse [51]. This is most likely to overturn all the efforts which had been put in place controlling Dengue and increases competition for the healthcare.…”
Section: Global Health System: the Unresolved Hurdlementioning
confidence: 99%
See 1 more Smart Citation
“…India's response to such acute public health emergency demonstrates the inadequate capacity of most dengue endemic countries (like Thailand, Cambodia, Bangladesh and Nigeria) in handling outbreaks and points to a healthcare system that is chronically underfunded, unregulated, and has inadequate infrastructure [49]. A similar study has confirmed a high societal and individual family burden of dengue in Cambodia [50].The emergence and reemergence of other viruses like filoviruses (Ebola) and coronaviruses (Covid-19) has strongly made the situation worse [51]. This is most likely to overturn all the efforts which had been put in place controlling Dengue and increases competition for the healthcare.…”
Section: Global Health System: the Unresolved Hurdlementioning
confidence: 99%
“…To address some of these challenges, humans are being used in preclinical trials which is ethically dangerous and has been underpinned by the non-existence of a licensed anti-dengue therapeutic agent that could treat a volunteer who becomes ill following challenge especially with non-protective wildtype DENV vaccination [57], [58]. In addition, Many new antiviral compounds against the NS5 protein of DENV are being investigated for example; the phosphoamidate nucleoside prodrug GS5734 also called "Remdesivir" (that is active against Ebola virus, arenaviruses, and coronaviruses) and "Favipiravir," as broadspectrum antivirals [51]. They are starting to show promising results.…”
Section: Challenges With the Development Of Vaccinesmentioning
confidence: 99%
“…RNA viruses like Corona, Ebola, Zika, and different strains of influenza A viruses mediate recent virus outbreaks that have been led to a considerable number of human deaths. Respiratory RNA viruses are highly contagious and result in occasional pandemic outbreaks and as well as the worldwide epidemics which happen annually ( Badolo et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%